Balinese Farmers Disensus in Koperasi Assistance For The Future of the Rural Economy - Wirawan, I Dewa Gede Kresna; Firmani, Putu Siti; Kharisma Pradana, Gede Yoga (Riwayat: Educational Journal of History and Humanities, 2025)
This research aims to analyze the future of the rural economy based on the role of Koperasi and Balinese farmers. In Bali, quite a few Balinese farmers contribute to the rural economy. Many Balinese farmers are members of Koperasi. On the other hand, some Balinese farmers are still experiencing a crisis. Koperasi have played a role in the economic problems of Balinese farmers. The problems are : 1) What is the level of effectiveness of the role of Koperasi for the needs of Balinese farmers?; 2) Is there a dissensus among Balinese farmers regarding Koperasi programs that are promising in rural development?. This research was completed using mixed methods. Respondents were determined based on a parallel sequential sampling technique. Primary data was collected through surveys with the help of questionnaires. Secondary data was obtained based on a literature study. All data was analyzed statistically and interpretatively with the help of S.P.S.S. The research results show : 1) There is evidence of the effectiveness of cooperatives' role in overcoming Balinese farmers' economic problems. There is a positive and significant influence on the role of cooperatives on the needs of Balinese farmers ( = 1.450, p = 0.026); 2) Balinese farmers have a dissensus regarding the future of a rural economy that is representative of the digital economy. These resistance symptoms are related to the failure of cooperative programs such as technological training ( = 0.585, p = 0.292), paranoid conditions, skepticism, problems using tools, and other choices of Balinese farmers.